2014
DOI: 10.1002/adhm.201300575
|View full text |Cite
|
Sign up to set email alerts
|

Three‐Dimensional Paper‐Based Model for Cardiac Ischemia

Abstract: In vitro models of ischemia have not historically recapitulated the cellular interactions and gradients of molecules that occur in a 3D tissue. This work demonstrates a paper-based 3D culture system that mimics some of the interactions that occur among populations of cells in the heart during ischemia. Multiple layers of paper containing cells, suspended in hydrogels, are stacked to form a layered 3D model of a tissue. Mass transport of oxygen and glucose into this 3D system can be modulated to induce an ische… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
121
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 126 publications
(130 citation statements)
references
References 52 publications
1
121
0
1
Order By: Relevance
“…In addition, 2D monotypic cultures do not resemble the complex cellular composition of the adult heart, where CMs represent only one third of the total number of cells: they are normally incorporated within networks of smooth muscle cells/pericytes, endothelial cells and fibroblasts (Tirziu et al , 2010) and covered by epicardium on the outside and endocardium on the inside layer. The generation of cardiac microtissues (Beauchamp et al , 2015), engineered heart tissues (Zimmermann and Schneiderbanger, 2002; Turnbull et al , 2014) or 3D vascularized cardiac layers (Mosadegh et al , 2014) have been reported. These multidimensional and heterogeneous environments promote CM organization and maturity and will thus probably contribute, in the future, to enhancing the predictivity and reliability of these platforms for drug screening when compared with 2D cultures (Eder et al , 2016).…”
Section: Assays and Readoutsmentioning
confidence: 99%
“…In addition, 2D monotypic cultures do not resemble the complex cellular composition of the adult heart, where CMs represent only one third of the total number of cells: they are normally incorporated within networks of smooth muscle cells/pericytes, endothelial cells and fibroblasts (Tirziu et al , 2010) and covered by epicardium on the outside and endocardium on the inside layer. The generation of cardiac microtissues (Beauchamp et al , 2015), engineered heart tissues (Zimmermann and Schneiderbanger, 2002; Turnbull et al , 2014) or 3D vascularized cardiac layers (Mosadegh et al , 2014) have been reported. These multidimensional and heterogeneous environments promote CM organization and maturity and will thus probably contribute, in the future, to enhancing the predictivity and reliability of these platforms for drug screening when compared with 2D cultures (Eder et al , 2016).…”
Section: Assays and Readoutsmentioning
confidence: 99%
“…Subsequent studies from the same research group have expanded the filter paper method to include a polyethylene (terephthalate) substrate and to have the ability to analyze the effects of soluble compounds on cell behavior [22,23]. An additional study used the system to study ischemia in cardiomyocytes [24].…”
Section: Introductionmentioning
confidence: 99%
“…[2] In recent years, paper has become increasingly interesting as a material in new applications. [3][4][5] For example, we and others have used it for microfluidic [6][7][8][9][10] and electroanalytical devices as the basis for low-cost diagnostics, [11,12] as 3-D scaffolds for cell growth, [13][14][15] as a substrate for printed electronics, [16][17][18][19][20][21][22] and in micro-electromechanical systems (MEMS). [16,23,24] A missing component for paper-based devices is an electrically controlled actuator that is embedded within the paper, can be fabricated by printing, and continues to operate when the paper that supports it is creased and/or folded.…”
Section: Introductionmentioning
confidence: 99%